Pengelolaan Website Sebagai Sistem Informasi Manajemen di Madrasah Aliyah Negeri Balikpapan - Bisma Arief Satria Putra; Bahrani Bahrani; Mohammad Salehudin (Journal on Education, 2024)
The aim of this research is to find out how effective the results are through developing thematic learning modules containing traditional games for the independence of class III at SDN 1 Kepoh. This research uses quantitative research methods. The research method explains the design of this research activity which was carried out at one of the elementary schools in Blora Regency, namely at SDN 1 Kepoh. Researchers chose SDN 1 Kepoh as a place for observations, interviews, product validation and product trials on class III students. design experiment with one group pretest posttest type. The design is used to compare results before and after treatment. Experimental research methods refer to research methods used to find the effect of certain treatments on others under controlled conditions.This research uses validity test instruments. Testing the reliability of study materials is based on the opinions or considerations of related experts. Data collection techniques using the Shapiro-Wilk normality test were used in this research to evaluate the null hypothesis. The research results show that the effectiveness tests carried out included the normality test, paired sample T test, and N-Gain test. The results of the normality test show normal values ​​and in the paired sample T-test the significance value is 0.000, meaning that there is a significant difference in the pre-test and post-test. And in the N-Gain test, the mean N-gain score was 0.4601, so the test results can be categorized as moderate. So it can be concluded that the test results of the effectiveness of thematic media modules containing traditional games in increasing the learning independence of class III students are in the moderate or sufficient category.